The Student's Introduction to Mathematica and the Wolfram Language - Torrence, Bruce F. 1963 Bruce Follet; Torrence, Eve A. 1963- (Eve Alexandra) (Cambridge University Press, 2019)
The unique feature of this compact student's introduction to Mathematica® and the Wolfram Language is that the order of the material closely follows a standard mathematics curriculum. As a result, it provides a brief introduction to those aspects of the Mathematica® software program most useful to students. Used as a supplementary text, it will help bridge the gap between Mathematica® and the mathematics in the course, and will serve as an excellent tutorial for former students. There have been significant changes to Mathematica® since the second edition, and all chapters have now been updated to account for new features in the software, including natural language queries and the vast stores of real-world data that are now integrated through the cloud. This third edition also includes many new exercises and a chapter on 3D printing that showcases the new computational geometry capabilities that will equip readers to print in 3D.